Pengaruh Pendekatan Realistic Mathematics Education (RME) Berbantuan GeoGebra Terhadap Kemampuan Penalaran Matematika Siswa Pada Materi Statistika Kelas X SMKN 6 Medan T.A 2025/2026 - Dinda Saktiana Simanullang; Agusmanto Hutauruk; Samuel Juliardi Sinaga (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach assisted by GeoGebra on students' mathematical reasoning skills in statistics material in class X at SMKN 6 Medan. The research employed a quasi-experimental method, with a population consisting of all grade X students divided into 8 classes. The sample was selected using cluster random sampling, resulting in class X MPLB 1 as the experimental group and class X TKKR 2 as the control group. Data were collected using a mathematical reasoning skills test. Data analysis using normality, homogeneity, and t-tests showed a significant difference between the post-test scores of mathematical reasoning skills in the two classes, with a significance value (2-tailed) of 0.001 < 0.05. The average post-test score of the experimental class reached 53.50, while the control class was 45.50, indicating that the mathematical reasoning skills of students taught with the RME approach assisted by GeoGebra were higher than those taught with conventional learning. Based on the Effect Size (Cohen's d) calculation, a value of 0.633 was obtained, which means that the use of the Realistic Mathematics Education (RME) approach assisted by GeoGebra provides a contribution or effect in the medium category to students' mathematical reasoning skills.